A Critical Analytical Study of Scientific Literature on the Role of Public Relations in Enhancing Institutional Performance in Middle Schools - Ali Muhammad Hasan Al-Sharif (Permata : Jurnal Pendidikan Agama Islam, 2025)
This research paper presents a critical analysis of the scholarly literature that has addressed the role of public relations in middle schools as a strategic tool to enhance the quality of institutional and communicative performance within the school environment. The study aims to explore how researchers and educational specialists have approached the concept of public relations, identify prevailing research trends, and uncover existing knowledge and methodological gaps in previous studies. The paper adopts the Literature Review Analysis method using a descriptive-analytical approach and reviews thirty peer-reviewed Arabic and international academic sources. The findings reveal that public relations serve as a vital tool for building a positive image of the school and strengthening trust with parents and the local community. However, its practice in middle schools still suffers from weak structuring, shortcomings in communication strategies, and a lack of professional specialization. The paper concludes with a set of practical and research-oriented recommendations to further develop this critical role.